(untitled) (Archives of Mechanics - Test, 2005)
This paper examines the mechanics of wing-cracks that are located at its extremities of an interface region with Coulomb friction. The region containing the interface and the wing-cracks is first subjected to an isotropic compression, which induces closure of the interface region. The region is then subjected to a uniaxial compression in an incremental fashion. Since the frictional effects are restricted to pre-defined surfaces, the boundary element technique can be applied quite successfully to determine the influence of Coulomb friction on the development of stress intensity factors at the tips of the wing-cracks.